Learning to think for ourselves: knowledge improvement and social benefits among farmer field school participants in Cameroon - David, S. (2007)
A case study of farmers who attended cocoa integrated crop and pest management (ICPM) farmer field schools in Cameroon and non-participating farmers provides empirical results on areas where there are gaps and mixed results in the FFS literature. FFS provided farmers with new skills and knowledge on cocoa ICPM and FFS graduates demonstrated superior knowledge on cocoa ICPM generally compared to non-FFS farmers. However, the tendency of FFS participants to retain and diffuse new skills and practices more than concepts and principles suggests the need to review aspects of the training. Forty-nine FFS graduates spontaneously provided hands-on informal training to 193 other farmers on key ICPM practices, demonstrating the contribution of farmer-to-farmer diffusion to scaling up farmer training. The case study suggests that FFS can be a starting point for farmer empowerment, but points out that social and technical outcomes can only be sustained if the appropriate local and national level institutions, support systems and policies related to agricultural extension and research are developed. The paper also highlights methodological issues related to measuring the social impacts of FFS.